The technique of point visualization of the electric field in space and time - Z. M. Kurbanismailov; A. T. Tarlanov; E. M. Akimov (Российский технологический журнал)
Testing of electronic devices is an integral part of the technological process of any manufacturer of such equipment. In this case, an electronic device is understood as an energy-intensive unit such as a mobile phone, data center or spacecraft. One of the key stages of testing is to identify the effect of electric fields on various electronic components of the device. This stage often requires making a mock-up of some part of an unfinished device in order to fix interference with special equipment. This requires time, financial and human resource costs. In order to reduce these costs in the modern world, the use of mathematical modeling tools for testing noise immunity and electromagnetic compatibility is becoming popular. In this paper, it is proposed to use an algorithm for visualizing electric fields in three-dimensional space and time. The algorithm is easily embedded into applications as a component of a mathematical modeling system. The work considered three ways of visualizing the electric field strength: starting from a simple setting of points in space, on the basis of which the electric field will be built, around the source of electric field radiation, to the use of algorithms that make it possible to arrange points equidistantly based on a given number of points in space for the formation of an electric field. The performance and visual implications of these methods were analyzed. The proposed methodology will be useful to the developer community as an embedded solution for point visualization of the electric field in any project in any algorithmic language with the ability to animate in time.